“Contributing to something good”: rural Latinx college students’ giving back through STEMM degrees and careers - Puente, Mayra; Romero, Melissa; Rios Arroyo, Daniel; Gutierrez-Serrano, Gabby (Frontiers in Education, 2025)
IntroductionThe U.S. prioritizes the development of STEMM talent, often framing its value through an individualistic and capitalist lens. This approach may not align with rural students’ values, ethics, and way of life, particularly for rural Latinx students, who often come from collectivist cultures. Accordingly, this article investigates how rural Latinx students’ intersectional identities and geographical backgrounds influence their STEMM degree and career pursuits, and desire to give back to their migrant farm worker communities.MethodsThis qualitative research study used Chicana/Latina feminist pláticas (conversations) methodology to examine the chosen STEMM majors, experiences, and future career intentions of five rural Latinx third-year undergraduate students from migrant farm worker backgrounds. This methodology fosters open-ended, culturally relevant conversations that allow students to highlight topics that matter most to them. Each plática ranged between 90 and 120 minutes and was audio recorded and transcribed.ResultsThree findings explained how rural Latinx students’ intersectional identities and geographical backgrounds influenced their desire to give back to their communities through STEMM degrees and careers. These included: (a) helping and leading through STEMM extracurricular activities, (b) pursuing socially conscious STEMM careers, and (c) addressing place-based inequities in rural communities.DiscussionRural Latinx students’ desires to “give back” outweighed commonly emphasized factors like job stability, career prestige, and high earnings—factors that, while important, were secondary to the students in this study. Higher education institutions must expand their programs, services, and curricula to better align with rural Latinx students’ diverse identities, values, and motivations for STEMM.